Comparing the cytotoxicity of electronic cigarette fluids, aerosols and solvents - Behar, Rachel Z (Tob Control, 2017)
BACKGROUND: As thousands of electronic cigarette (e-cigarette) refill fluids continue to be formulated and distributed, there is a growing need to understand the cytotoxicity of the flavouring chemicals and solvents used in these products to ensure they are safe. The purpose of this study was to compare the cytotoxicity of e-cigarette refill fluids/solvents and their corresponding aerosols using in vitro cultured cells. METHODS: E-cigarette refill fluids and do-it-yourself products were screened in liquid and aerosol form for cytotoxicity using the MTT (3-(4,5-dimethylthiazol2-yl)−2,5-diphenyltetrazolium bromide) assay. The sensitivity of human pulmonary fibroblasts, lung epithelial cells (A549) and human embryonic stem cells to liquids and aerosols was compared. Aerosols were produced using Johnson Creek’s Vea cartomizer style e-cigarette. RESULTS: A hierarchy of potency was established for the aerosolised products. Our data show that (1) e-cigarette aerosols can produce cytotoxic effects in cultured cells, (2) four patterns of cytotoxicity were found when comparing refill fluids and their corresponding aerosols, (3) fluids accurately predicted aerosol cytotoxicity 74% of the time, (4) stem cells were often more sensitive to aerosols than differentiated cells and (5) 91% of the aerosols made from refill fluids containing only glycerin were cytotoxic, even when produced at a low voltage. CONCLUSIONS: Our data show that various flavours/brands of e-cigarette refill fluids and their aerosols are cytotoxic and demonstrate the need for further evaluation of e-cigarette products to better understand their potential health effects.